Learning to Diagnose With Simulations 2022
DOI: 10.1007/978-3-030-89147-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Mathematical Argumentation Skills: A Video-Based Simulation for Pre-Service Teachers

Abstract: Mathematical argumentations and proofs cause difficulties for secondary school students (Healy and Hoyles, 2000). Teachers’ diagnostic skills are essential for adapting their teaching to students’ specific needs in order to facilitate students’ understanding of proofs (Südkamp and Praetorius, 2017). We developed a video-based simulation to investigate and promote pre-service teachers’ diagnostic skills. Participants encountered a diagnostic task with short, scripted video clips showing simulated students worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As an example, when teaching the human circulatory system in biology education, research has identified a number of typically occurring student (mis)conceptions which can promote or hinder a deep understanding (Van Lehn et al, 2003;Graesser et al, 2011;Dorfner et al, 2019;Scharfenberg and Bogner, 2019;Kramer et al, 2020). This evidence can be used for video case design by presenting students who saliently model these conceptions in their verbal interactions with a teacher (Codreanu et al, 2022). In addition, science education research has identified a number of teaching situations in which these kinds of conceptions can become particularly salient, for example, when teachers elicit and guide student thinking in small group situations (Park and Chen, 2012;Kloser, 2014).…”
Section: First Draftmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, when teaching the human circulatory system in biology education, research has identified a number of typically occurring student (mis)conceptions which can promote or hinder a deep understanding (Van Lehn et al, 2003;Graesser et al, 2011;Dorfner et al, 2019;Scharfenberg and Bogner, 2019;Kramer et al, 2020). This evidence can be used for video case design by presenting students who saliently model these conceptions in their verbal interactions with a teacher (Codreanu et al, 2022). In addition, science education research has identified a number of teaching situations in which these kinds of conceptions can become particularly salient, for example, when teachers elicit and guide student thinking in small group situations (Park and Chen, 2012;Kloser, 2014).…”
Section: First Draftmentioning
confidence: 99%
“…The design and use of micro-teaching situations can be viewed in light of such simulation development. A microteaching mock-up can provide a simulated setting wherein underlying core teaching concepts can be realized as decomposed yet still authentic scenarios (Codreanu et al, 2022).…”
Section: First Draftmentioning
confidence: 99%